Neurodegeneration with Brain Iron Accumulation: An Overview - TONEKABONI*, Seyed Hassan; MOLLAMOHAMMADI, Mohsen (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Tonekaboni SH, Mollamohammadi M. Neurodegeneration with Brain Iron Accumulation: An Overview. Iran J Child Neurol. 2014 Autumn;8(4): 1-8. Abstract Objective Neurodegeneration with brain iron accumulation (NBIA) is a group of neurodegenerative disorder with deposition of iron in the brain (mainly Basal Ganglia) leading to a progressive Parkinsonism, spasticity, dystonia, retinal degeneration, optic atrophy often accompanied by psychiatric manifestations and cognitive decline. 8 of the 10 genetically defined NBIA types are inherited as autosomal recessive and the remaining two by autosomal dominant and X-linked dominant manner. Brain MRI findings are almost specific and show abnormal brain iron deposition in basal ganglia some other related anatomical locations. In some types of NBIA cerebellar atrophy is the major finding in MRI. References Shevel M. Racial hygiene, activeeuthanasia, and Julius Hallervorden. Neurology 1992;42:2214-2219. HayflickSJ. Neurodegeneration with brain Iron accumulation: from genes to pathogenesis.Semin Pediatr Neurol 2006;13:182-185. Zhou B, Westawy SK, Levinson B, et al. A novel pantothenate kinase gene(PANK2) is defective in Hallervorden-Spatzsyndrome. Nat Genet 2001;28:345- 349. www.ncbi.nlm.nihgov/NBK111Y/university of Washington, seattle. Allison Gregory and Susan Hayflick. Paisan-Ruiz C, Li A, Schneider SA, et al. Widesread Levy body and tau accumulation in childhood and adult onset dystonia-parkinsonism cases with PLA2G6 mutations. Neurobiol Aging 2012;33:814-823. Dick KJ, Eckhardt M, Paison-Ruiz C, et al. Mutation of FA2H underlies a complicated form of hereditary spastic paraplegia(SPG 35). Hum Mutat 31: E1251-E1260. Edvardson S, Hama H, Shaag A, et al. Mutation in the fatty acid 2-Hydroxylase gene are associated with leukodystrophy with spastic paraparesis and dystonia. Am I Hum Genet 2008;83:647-648. Schneider SA, Aggarwal A, Bhatt m, et al. Severe tongue protrusion dystonia: clinical syndromes and possible treatment. Neurology 2006;67: 940-943. Egan RA, Weleber RG, Hogarth P. et al. Neuroopthamologic and electroreinographic finding in pantothenate kinase associated neurodegeneration. Am J ophtalmol 2005;140:167-274. Kruer MC, Boddaert N. Adiadnostic Algorithm. Semin Pediatrn Neurol 2012;19: 67-74. Dezfouli MA, Alavi A, Rohani M, Rezvani M, Nekuie T, Klotzle B, Tonekaboni SH, Shahidi GA, Elahi E. PANK2 and C19orf12 mutations are common causes of neurodegeneration with brain iron accumulation. Mov Disord 2013 Feb;28(2):228-32. doi: 10.1002/mds.25271.Epub 2012 Nov 19. Hartig MB, Hortnagel K, Garavaglia B, et al. Genotype and phenotypic spectrum of PANK2 mutations in patients with neurodegeneration with brain iron accumulation Ann Neurol 2006;59: 248-256. Kotzbauer PT, Truax AC, Trojanowsli JQ, et al. Altered neuronal mitochondrial coenzyme A synthesis in neurodegeneration with brain iron accumulation cause by abnormal processing of mutant pantothenase Kinase2. J Neurosci 2005;25:689-698. Poli M, Deosas M, Lusciete S, et al. Pantothenate Kinase2 silencing causes cell growth reduction and iron deregulation Neurobiol Dis 2010;39: 204-210. Wakabayashi K, Fukushima T, Koide R, et al. Juvenile-nset generalized neuroaxonal dystrophy with diffuse neurofibrillary and Lewy body pathology. ActaNeuropathonal 2000;99: 331-336. Galvin JE, Giasson B, Hurting HI, et al. Neurodegeneration with brain iron accumulation, type1 is characterized by alpha, beta and gamma-synuclein neuropathology, Am T Pathol 2000;157: 361-368. Li A, Paudel R, Johnson R, et al. Pantothenate Kinaseassocated neurodegeneration is not a synucleinopathyneuropathol Appl Neurobiol(in press). Gregory A, Polster BJ, Hayflick SJ: Clinical and genetic delineation of neurodegeneration with brain iron accumulation. J Med Genet 2009;46:73-80. Gregory A, Westaway SK, Holm IE, et al. Neurodegeneration associated with genetic defects in phospholipase A2. Neurology 2008;71:1402-1409. Harting MB, Lsao A, Haa KT, et al. Absence of an orphan mitochondrial protein, c19orf12 with brain iron accumulation, Am J Hum Genet 2011;89: 543-550. Najim al-Din AS, Wriekat A, Mubaidin A, et al. Pallidopyramidal degeneration, supraneuclearupgaze paresis and dementia: Kufor- Rakeb syndrome. Acta Neurol Scand 2011;89: 347-352. Tobias B Hoak, Penelope Hogarth, Micheal C Kruer et al. Am J Hum Genet 2012 Dec 7; 91 (6): 1144-49. Chummery PF, Crompton DE, Bircholl D, et al. Clinical features and matural history of Neuroferritinopathy caused by the FTL1 gene mutation. Brain 2007;130:110-119. Mc Neil A, Bircholl D, Hayflich SJ, et al. T2 and FSE MRI distinguishes L subtypes of NBIA, Neurology 2008;70: 1614- 1619. McNeil A , Pandolfo M, Kuhn J,et al.The Neurological presentation of ceruloplasmin gene mutations. Eur Neurol 2008;60:200-205. Dusi S, Valletta L, Hoach TB, et al. Exone sequencing reveals mutations in Co A synthtas as a cause of neurodegeneration with brain iron accumulation: Am J Hum Genetic Jan2, 2014. Aras M Alazim, Amir Alsaif, Abdulaziz Al-Semari, et al. mutation in C2 orf 37, cause hypogonadism, diabetes Melitus, Mental retardation and extrapyramidal syndrome: Am J Hum Genetic. 2008 Dec 12; 83(6): 684-691.